Induction of broad multifunctional CD8+ and CD4+ T cells by hepatitis B virus antigen-based synthetic long peptides ex vivo - Jansen, Diahann T. S. L.; de Beijer, Monique T. A.; Luijten, Robbie J.; Kwappenberg, Kitty; Wiekmeijer, Anna-Sophia; Kessler, Amy L.; Pieterman, Roel F. A.; Bouzid, Rachid; Krebber, Willem-Jan; de Man, Robert A.; Melief, Cornelis J. M.; Buschow, Sonja I. (Frontiers in Immunology, 2023)
SIB collaborates with and receives co-funding from ISA Pharmaceuticals B.V., Oegstgeest, the Netherlands. SIB, DTSLJ, MTAdB, ASW, WJK and CJMM are listed as inventors on a patent application related to the work in this manuscript on novel long peptide antigens for treatment of hepatitis B related disease, filled by ISA Pharmaceuticals B.V. CJMM and WJK have a stock appreciation right in the issued share capital of ISA Pharmaceuticals. CJMM, WJK and ASW are employed by ISA Pharmaceuticals. CJMM reports holding patents with ISA Pharmaceuticals. The authors declare no further conflicts of interest. Financial support statement This work was financed by the Dutch Ministry of Economic Affairs and Climate Policy by means of the public private partnership (PPP) allowance from the Top Sector Life Sciences & Health to stimulate publicprivate partnerships in conjunction with the Dutch Digestive Foundation (LSHM16056). In the latter, ISA Pharmaceuticals B.V. Leiden, the Netherlands, is the collaborating and co-funding private partner.epitopes is a promising treatment strategy for chronic hepatitis B infection (cHBV).We designed SLPs for three HBV proteins; HBcAg and the non-secreted proteins polymerase and X and investigated their ability to induce T cell responses ex vivo. A set of 17 SLPs was constructed based on viral protein conservation, functionality, predicted and validated binders for prevalent Human Leukocyte antigen (HLA) supertypes, validated HLA I epitopes and chemical producibility. All 17 SLPs were capable of inducing IFNɣ production in samples from four or more donors that resolved an HBV infection in the past (resolver). Further analysis of the best performing SLPs demonstrated activation of both CD8+ and CD4+ multi-functional T cells in one or more resolver and patient sample(s). When investigating which SLP could activate HBV-specific T cells, the responses could be traced back to different peptides for each patient or resolver. This indicates that a large population of subjects with different HLA types can be covered by selecting a suitable mix of SLPs for therapeutic vaccine design.In conclusion, we designed a set of SLPs capable of inducing multifunctional CD8+ and CD4+ T cells ex vivo that create important components for a novel therapeutic vaccine to cure cHBV.